Measurement and Comparison of Glass Transition and Sticky Point Temperatures of Distillers Dried Grains with Solubles (DDGS) with Varying Condensed Distillers Solubles (CDS) and Drying Temperature Levels - Bhadra, Rumela; Rosentrater, Kurt A.; Muthukumarappan, Kasiviswanath (My University, 2014)
Distillers dried grains with solubles (DDGS) is the main coproduct of the U.S. fuel ethanol industry and has significantly impacted the livestock feed markets in recent years. Particle agglomeration and subsequent flowability problems during storage and transport are often a hindrance, a nuisance, and expensive. This paper aims at characterizing the glass transition (Tg) and sticky point (Ts) temperatures of DDGS samples prepared with varying condensed distillers solubles (CDS) levels (10, 15, and 20%, wb), drying temperatures (100, 200, and 300°C), and moisture contents (0, 10, and 20%, db), and it discusses implications on DDGS flowability behavior. Distillers wet grains were combined with specified levels of CDS and dried in a convection-style laboratory oven to produce DDGS. Subsequently, predetermined amounts of water were added to the DDGS to achieve desired moisture content levels. To determine Tg (°C), a differential scanning calorimeter was used, whereas Ts (°C) was determined through a novel technique with a rheometer. Results indicated high correlations between observed Ts and observed Tg (R2 = 0.87) data for DDGS samples. Also, the empirical model for predicted Tg = f (drying temperature, CDS level, and moisture content) based on the Gordon–Taylor model showed favorable R2 (0.74). Stickiness of DDGS increased with an increase in moisture content, indicating flow problems resulting from moisture. It was found that drying temperatures and CDS levels each had significant effects on Tg and Ts as well.
Citation: Bhadra, R., K. Muthukumarappan, and K. A. Rosentrater. 2014. Measurement and Comparison of Glass Transition and Sticky Point Temperatures of Distillers Dried Grains with Solubles (DDGS) with Varying Condensed Distillers Solubles (CDS) and Drying Temperature Levels. Cereal Chemistry 91(4):406-413.